Rigler’s triad - Chinelli, Javier; Rodríguez Temesio, Gustavo (Cirugía del Uruguay, 2020)
68-year-old patient, with no surgical history. He was admitted to the Emergency Department with a clinical picture of intestinal occlusion. A simple abdominal radiograph was requested (only obtained in decubitus), observing the presence of Rigler's radiological triad, pathognomonic of the biliary ileum. The 3 elements are indicated: dilated thin handles (black arrow), aerobilia (white arrow) and the ectopic calcified stone in the right iliac fossa (yellow arrow). Gallstone ileus is intestinal occlusion as a consequence of the migration of a gallstone through a bilio-digestive fistula and its impaction, frequently at the level of the ileo-cecal valve. Usually it is a cholecysto-duodenal fistula, although it can also be a cholecysto-colonic fistula. The classically described clinical picture is that of intermittent occlusion, being more frequent in elderly patients, with a long history of symptomatic biliary lithiasis.